Immunobiological activities of a 55-kilodalton cell surface protein of Prevotella intermedia ATCC 25611. - Matsushita, K (1994)
A protein was extracted from whole cells of Prevotella intermedia ATCC 25611 with sodium lauroylsarcosine and purified by chromatography on a DEAE-Sepharose fast-flow column. The The apparent molecular weight of the protein was 55,000. A mouse polyclonal antibody specific for the protein recognized the cell surface structure of P. intermedia and also reacted with proteins in lysates of other black-pigmented anaerobic bacteria, such as Porphyromonas endodontalis and Prevotella melaninogenica, but not with those in lysates of Porphyromonas gingivalis or with the purified fimbriae of P. gingivalis 381. The N-terminal sequence of the 55-kDa protein showed only low homology with the cell surface proteins of any black-pigmented bacteria reported to date. The level of immunoglobulin G antibody to the antigen was higher in the sera of patients with periodontitis than in the sera of healthy volunteers. The protein induced interleukin-1 alpha, -1 beta, -6, and -8 and tumor necrosis factor alpha in human peripheral blood mononuclear cell cultures and interleukin-1 beta and -6 in human umbilical vascular endothelial cell and gingival fibroblast cultures. The protein induced interleukin-6 and tumor necrosis factor alpha activities in peritoneal macrophages from C3H/HeJ as well as from C3H/HeN mice and also induced cytokine activities in the sera of both strains of mice primed with muramyldipeptide.